The Influence of Training, Human Resource Development, and Competence on the Performance of Sleman District MSMEs - Viky Ridwantoro; Rinaldi Rinaldi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Micro, Small, and Medium Enterprises (MSMEs), as a pillar of the economy, contribute to the state budget. Training, human resource development, and competence are important strategies for shaping good and optimal business performance. This study aims to analyze the effect of training, human resource development (HR), and competence on the performance of micro, small, and medium enterprises (MSMEs) in the Sleman Regency. The study used a descriptive quantitative approach with data collection through questionnaires distributed online to 200 culinary MSME players in Sleman using Google Forms. The sampling technique used was non-probability, as was the quota sampling method. All data obtained has gone through validity and reliability tests to ensure the quality of the instrument. Data were analyzed using descriptive analysis and multiple linear regression at a significance level of 5% (α = 0.05). The analysis prerequisite tests include normality, multicollinearity, and heteroscedasticity tests. Hypothesis testing used t-test and F-test. The main findings of this study show that (1) training has a positive and significant effect on the performance of MSME actors; (2) HR development has a positive and significant effect on the performance of MSMEs; (3) competence has a positive and significant effect on the performance of MSME actors; and (4) simultaneously, the three variables of training, HR development, and competence have a significant effect on improving the performance of MSMEs in Sleman Regency. This shows that 77.7% of the performance of MSME actors is influenced by the variables of training, HR development and competence, the remaining 22.3% of the performance of MSME actors is influenced by other factors that have not been examined in this study.